A typical case had rare immediate and delayed red man syndrome multiple times after norvancomycin injection: A case report. Issue 47 (25th November 2022) - Zang, Tianying; Liu, Bingyang; Ma, Lunkun; Tang, Xiaojun
Abstract : Background: Red man syndrome (RMS) is an adverse effect of vancomycin that usually occurs within minutes to tens of minutes after infusion. Previous literature reported that RMS rarely occurs again after the infusion speed is controlled. Methods: We report a case of immediate and delayed RMS that presented with fever, persistent lower extremity rash, shock, lymphadenopathy and pulmonary edema. This patient subsequently diagnosed with Sjögren's Syndrome, the time from NVCM infusion to RMS onset of this case ranged from 10 minutes to 54 hours, which are all rare in clinic and hard to distinguish severe RMS and IgE-mediated anaphylaxis. Results: After multidisciplinary consultation, the patient was diagnosed with RMS based on clinical manifestations and laboratory results. Patients' symptoms, signs, body temperature and disease progress were monitored, and an active search for causes was conducted. After a 20-day treatment, all the symptoms disappeared, the patient was transferred to immunology department to treat SS. Conclusion subsections: We reported a patient repeatedly developed fever and even shock when the infusion speed is normal, which was rare and similar as anaphylaxis. Therefore, the progression of RMS and its differentiation from allergy need to be further studied.